Water in the house - women's work - Sally Sutton (2001)
It has been a struggle of the past three decades to promote the involvement of women in decision-making in rural water supply. This may have now reached a stage where paradoxically more emphasis needs to be placed on men’s roles. A quiet revolution is taking place, in that men are becoming more prepared to assist in water collection, and this needs to be brought out, so that others can see that it is increasingly normal behaviour, and does not have to lead to loss of dignity, or ridicule. The role of women in decision-making still needs to be promoted, but this should not be so laboured that men feel they have no role to play and no responsibility. In practical terms, this paper also looks at how effective women in rural Zambia are being in providing safe and adequate water in the house, and in promoting good personal hygiene within the family. Information is based on data collected during base-line surveys in smaller poorer communities which mostly still use traditional water sources. It indicates that in hygiene education in the areas studied, that more emphasis might be put on water storage capacity and children’s hand washing, and less on water collection and storage practice.